RÚt gọn:
A=( \(\frac{a^2-a}{a-1}-1\)) ( \(\frac{a^2+a}{a+1}+1\))
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Trả lời
\(B=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}.\left(\frac{1}{a^2+2a+1}-\frac{1}{a^2-1}\right)\) \(\left(a\ge0.a\ne1\right)\)
\(B=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}.\left[\frac{1}{\left(a+1\right)^2}-\frac{1}{\left(a-1\right).\left(a+1\right)}\right]\)
\(B=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}.\left[\frac{a-1-a-1}{\left(a+1\right)^2.\left(a-1\right)}\right]\)
\(B=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}.0\)
\(B=\frac{1}{a+1}\)
Vậy \(B=\frac{1}{a+1}\)
\(B=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}\left(\frac{1}{a^2+2a+1}-\frac{1}{a^2-1}\right)ĐK\left(a\ge0;a\ne1\right)\)
\(=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}\left(\frac{a^2-1}{\left(a^2+1\right)\left(a^2-1\right)}-\frac{a^2+1}{\left(a^2-1\right)\left(a^2+1\right)}\right)\)
\(=\frac{1}{a+1}+\frac{a-a^3}{a^2+1}\left(\frac{a^2-1-a^2-1}{\left(a^2+1\right)\left(a^2-1\right)}\right)\)
\(=\frac{1}{a+1}\)
Vậy \(B=\frac{1}{a+1}\)
a, ĐK: \(a\ne0,b\ne0,a+b\ne0\)
\(A=\left[\frac{1}{a^2}+\left(\frac{1}{a}+\frac{1}{b}\right):\frac{a+b}{2}+\frac{1}{b^2}\right].\frac{a^2b^2}{a^3+b^3}:\left(a+b\right)\)
\(=\left[\frac{1}{a^2}+\frac{a+b}{ab}:\frac{a+b}{2}+\frac{1}{b^2}\right].\frac{a^2b^2}{a^3+b^3}:\left(a+b\right)\)
\(=\left[\frac{1}{a^2}+\frac{2}{ab}+\frac{1}{b^2}\right].\frac{a^2b^2}{a^3+b^3}:\left(a+b\right)\)
\(=\frac{\left(a+b\right)^2}{a^2b^2}.\frac{a^2b^2}{\left(a+b\right)\left(a^2-ab+b^2\right)}.\frac{1}{a+b}\)
\(=\frac{1}{a^2-ab+b^2}\)
b, \(a^2-ab+b^2=\left(a-\frac{1}{2}b\right)^2+\frac{3}{4}b^2>0\left(a,b\ne0\right)\)
\(\Rightarrow A=\frac{1}{a^2-ab+b^2}>0\forall a;b\)
\(\left(\frac{a}{a-1}-\frac{1}{a^2-a}\right):\left(\frac{1}{a+1}+\frac{2}{a^2-1}\right)=\left(\frac{a}{a-1}-\frac{1}{a\left(a-1\right)}\right):\left(\frac{1}{a+1}+\frac{2}{\left(a-1\right)\left(a+1\right)}\right)\)
\(=\frac{a^2-1}{a\left(a-1\right)}:\frac{a-1+2}{\left(a-1\right)\left(a+1\right)}=\frac{\left(a^2-1\right)\left(a-1\right)\left(a+1\right)}{a\left(a-1\right)\left(a+1\right)}=\frac{a^2-1}{a}=a-\frac{1}{a}\)
a) \(a^{\dfrac{1}{3}}\cdot a^{\dfrac{1}{2}}\cdot a^{\dfrac{7}{6}}=a^{\dfrac{1}{3}+\dfrac{1}{2}+\dfrac{7}{6}}=a^2\)
b) \(a^{\dfrac{2}{3}}\cdot a^{\dfrac{1}{4}}:a^{\dfrac{1}{6}}=a^{\dfrac{2}{3}+\dfrac{1}{4}-\dfrac{1}{6}}=a^{\dfrac{3}{4}}\)
c) \(\left(\dfrac{3}{2}a^{-\dfrac{3}{2}}\cdot b^{-\dfrac{1}{2}}\right)\left(-\dfrac{1}{3}a^{\dfrac{1}{2}}b^{\dfrac{2}{3}}\right)=\left(\dfrac{3}{2}\cdot-\dfrac{1}{3}\right)\left(a^{-\dfrac{3}{2}}\cdot a^{\dfrac{1}{2}}\right)\left(b^{-\dfrac{1}{2}}\cdot b^{\dfrac{2}{3}}\right)\)
\(=-\dfrac{1}{2}a^{-1}b^{-\dfrac{1}{3}}\)
\(B=\frac{a+1}{a^2-a+1}-\frac{1}{a+1}+\)\(\frac{a-2}{a^3+1}\)
\(B=\frac{\left(a+1\right)^2}{a^3+1}-\frac{a^2-a+1}{a^3+1}+\)\(\frac{a-2}{a^3+1}\)
\(B=\frac{a^2+2a+1-a^2+a-1-a+2}{a^3+1}\)
\(B=\frac{2a+2}{a^3+1}\)
\(B=\frac{2\left(a+1\right)}{\left(a+1\right)\left(a^2+a+1\right)}\)
\(B=\frac{2}{a+1}\)
\(B=\frac{a+1}{a^2-a+1}-\frac{1}{a+1}-\frac{a-2}{a^3+1}\) ĐKXĐ : \(x\ne-1\)
\(=\frac{\left(a+1\right)^2}{\left(a+1\right)\left(a^2-a+1\right)}-\frac{a^2-a+1}{\left(a+1\right)\left(a^2-a+1\right)}\)\(-\frac{a-2}{\left(a+1\right)\left(a^2-a+1\right)}\)
\(=\frac{a^2+2a+1-a^2+a-1-a+2}{\left(a+1\right)\left(a^2-a+1\right)}\)
\(=\frac{\left(a^2-a^2\right)+\left(2a+a-a\right)+\left(1-1+2\right)}{\left(a+1\right)\left(a^2-a+1\right)}\)
\(=\frac{2a+2}{\left(a+1\right)\left(a^2-a+1\right)}\)
\(=\frac{2\left(a+1\right)}{\left(a+1\right)\left(a^2-a+1\right)}\)
\(=\frac{2}{a^2-a+1}\)
\(\text{GIẢI :}\)
ĐKXĐ : \(a\ne\pm1\).
\(M=\frac{1}{a^2-2a+1}-\left(\frac{a}{a^2-1}-\frac{1}{a^3-a}\right):\frac{a^2-2a+1}{a+a^3}\)
\(=\frac{1}{a^2-2a+1}-\left(\frac{a}{a^2-1}-\frac{1}{a\left(a^2-1\right)}\right):\frac{a^2-2a+1}{a+a^3}\)
\(=\frac{1}{a^2-2a+1}-\left(\frac{a^2}{a\left(a^2-1\right)}-\frac{1}{a\left(a^2-1\right)}\right):\frac{a^2-2a+1}{a+a^3}\)
\(=\frac{1}{a^2-2a+1}-\frac{a^2-1}{a\left(a^2-1\right)}:\frac{\left(a-1\right)^2}{a\left(1+a^2\right)}\)
\(=\frac{1}{a^2-2a+1}-\frac{\left(a-1\right)^2}{a\left(a^2-1\right)}\cdot\frac{a\left(a^2+1\right)}{1+a^2}\)
\(=\frac{1}{a^2-2a+1}-\frac{\left(a-1\right)^2}{1+a^2}=\frac{-a^2}{\left(a-1\right)^2}\).
\(\text{ĐKXĐ: }x\ne1\)
\(M=\frac{a^2+2}{a^3-1}+\frac{a+1}{a^2+a+1}-\frac{1}{a-1}=\frac{a^2+2}{\left(a-1\right)\left(a^2+a+1\right)}+\frac{a+1}{a^2+a+1}-\frac{1}{a-1}\)
\(=\frac{a^2+2}{\left(a-1\right)\left(a^2+a+1\right)}+\frac{\left(a-1\right)\left(a+1\right)}{\left(a-1\right)\left(a^2+a+1\right)}-\frac{a^2+a+1}{\left(a-1\right)\left(a^2+a+1\right)}\)
\(=\frac{a^2+2+a^2-1-a^2-a-1}{\left(a-1\right)\left(a^2+a+1\right)}=\frac{a^2-a}{\left(a-1\right)\left(a^2+a+1\right)}=\frac{a.\left(a-1\right)}{\left(a-1\right)\left(a^2+a+1\right)}\)
\(=\frac{a}{a^2+a+1}\)
\(\left(\frac{1}{2+2.\sqrt{a}}+\frac{1}{2-2.\sqrt{a}}-\frac{a^2+1}{1-a^2}\right).\left(1+\frac{1}{a}\right)\)
\(=\left(\frac{2-2.\sqrt{a}+2+2.\sqrt{a}}{\left(2+2.\sqrt{a}\right)\left(2-2.\sqrt{a}\right)}-\frac{a^2+1}{\left(1-a\right).\left(1+a\right)}\right).\left(\frac{a+1}{a}\right)\)
\(=\left(\frac{4}{4-4a}-\frac{a^2+1}{\left(1-a\right).\left(1+a\right)}\right).\left(\frac{a+1}{a}\right)=\frac{\left(1+a\right)}{\left(1-a\right).\left(1+a\right)}\cdot\frac{a+1}{a}=\frac{1+a}{\left(1-a\right).a}=\frac{a+1}{a-a^2}\)
\(A=\left(\frac{a^2-a}{a-1}-1\right)\left(\frac{a^2+a}{a+1}+1\right)\)
\(\Leftrightarrow A=\left(\frac{a\left(a-1\right)}{a-1}-1\right)\left(\frac{a\left(a+1\right)}{a+1}+1\right)\)
\(\Leftrightarrow A=\left(a-1\right)\left(a+1\right)\)
\(\Leftrightarrow A=a^2-1\)
Vậy \(A=a^2-1\)